PENGEMBANGAN PROGRAM TANAM JAGUNG PANEN SAPI (TJPS) YANG BERKELANJUTAN DI DESA MANUSAK KECAMATAN KUPANG TIMUR KABUPATEN KUPANG - Awa, Rambu Ana; Nurwiana, Ida; Chamdra, Santhy (Buletin Ilmiah Impas, 2023)
Corn development is part of the flagship program of the NTT provincial government known as the Cattle Harvest Corn Planting Program (TJPS) to increase corn production, cattle population, cattle population, welfare of farming families and breeders. This study aims to: 1) determine corn cropping program for cattle (TJPS) in Manusak Village, Eats Kupang District, 2) determine the sustainability of the corn cropping program for cattle (TJPS) in Manusak Village, East Kupang District form the economic, socio – cultural, technological, resource dimensions natural resource and institutional dimensions, 3) formulate the direction of development of the cow harvest corn panting program (TJPS) in Manusak Village, East Kupang District. Location determination is done deliberately. The population in this study were 40 members of the Farmer’s Group who participated in the TJPS program. The types of data used are primary data and secondary data. The analytical method uses descriptive quantitative analysis and RAPTJPS-multidimensional scaling (MDS). The resulst of the study show that: 1) the cow harvest corn planting program (TJPS) is one of the programs run by the NTT provincial government that has been implemented and has helped the farmers’ economy. 2) the sustainability of the TJPS program produces a sustainability index of 55% wich is included in the fairly sustainable category. 3) Leverage/sensitive factors that are a priority to pay attention to regarding the direction of the TJPS program development in Manusak Village are increasing the provision of water for irrigating corn and the need to increase the utilization of cow dung into organic fertilizer.